Effects of application of Kinesio Taping on the Tibialis Anterior muscle in Cerebral Palsy: case series (Research, Society and Development, 2022)
Justification: Cerebral palsy (CP) caused by injury to the immature Central Nervous System and causes repercussions as serious as the extent of the lesion. Equine foot is common in children with spastic CP, due to hyperactivity of the plantar flexors in relation to the main dorsoflexor, tibialis anterior. Treatment based on adaptations made to improve patients' quality of life. The Kinesio Taping® (KT®) method aims to maintain therapeutic results, being the functional correction technique widely used in neurological patients to limit unwanted or pathological movements. Objective: To observe the effects of KT® application on the tibialis anterior on spasticity levels and tibio-tarsal range of motion in CP. Methods: The descriptive observational study of the case series type, carried out from October 24th to November 31th 2014. Which seven children underwent assessment of spasticity of the right lower limb and of the right tibio-tarsal joint range of motion and intervention using the KT® method. Results: The final sample consisted of seven children aged between 7 and 14 years, one of which was female. Most children reduced or maintained the degree of spasticity, and increased plantar flexion at rest and ranges in dorsiflexion and plantar flexion. Conclusion: The results suggest that, although the participants did not demonstrate affinity with the technique, there was some interference of the Kinésio Taping® method in their spasticity and in their tibio-tarsal joint mobility.